Mental health challenges and work : advanced topics and future research directions - Rosado-Solomon, Emily H. (Routledge, 2026)
There is a growing recognition that poorly designed work can degrade employees' mental health. Relatedly, there is also an acknowledgment that employees with existing mental health challenges-such as clinically significant depression and anxiety-may need particular support to thrive in the workplace. Yet, while research on this topic has blossomed, there are systematic challenges that must be addressed to promote continued advancement.This book will go beyond the basics to investigate complex questions about the relationship between work and employees' mental health. For instance, how are employees' mental health challenges impacted by their gender or race? How can employees' mental health be protected in inherently stressful work? By juxtaposing curated research on mental health and work, this edited volume provides value by highlighting novel perspectives, as well as areas of opportunity to better understand how diverse employees manage mental health in the changing world of work.Researchers and advanced students in management and psychology will find that this book provides a strong foundation for conducting future studies at the intersection of work and mental health.Chapters 2 and 3 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.
Keywords: Industrial psychiatry.; Employees -- Mental health.; elektronické knihy; electronic books